2012
DOI: 10.1371/journal.pntd.0001733
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Taenia solium Cysticercosis in Rural Pigs of Northern Peru

Abstract: Taenia solium is a cestode parasite that causes cysticercosis in both humans and pigs. A serological survey was undertaken to assess the seroprevalence and risk factors associated with porcine cysticercosis in the rural district of Morropon, Peru. Pigs aged between 2 and 60 months were assessed by the Enzyme-linked Immunoelectrotransfer blot (EITB) assay to determine their serological status against porcine cysticercosis in a cross-sectional study. A total of 1,153 pigs were sampled. Porcine seroprevalence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
2
28
1
2
Order By: Relevance
“…During this period, all animals (previously infected or otherwise) are protected against new T. solium infection by the vaccine. A smilar result was obtained in a field trial conducted in Peru (Jayashi et al, 2012).…”
Section: Vaccination Of Pigsmentioning
confidence: 84%
See 1 more Smart Citation
“…During this period, all animals (previously infected or otherwise) are protected against new T. solium infection by the vaccine. A smilar result was obtained in a field trial conducted in Peru (Jayashi et al, 2012).…”
Section: Vaccination Of Pigsmentioning
confidence: 84%
“…Serological tests for the detection of specific antibodies or specific antigens use enzyme-linked immunosorbent assay (ELISA) and electro-immuno transfer blot (EITB) (Lightowlers et al, 2016). Most of the few serological studies of pigs in West Africa have used B158/B160 Ag-ELISA (Secka et al, 2010a;Ganaba et al, 2011) and studies of Weka et al (2009) (Jayashi et al, 2012;Devleesschauwer et al 2013;Lightowlers et al, 2016). Moreover, false positive or transient positive reactions might arise from exposure to T. solium eggs that did not develop to cysticerci to be detected at carcass inspection (Lightowlers et al, 2016).…”
Section: Serology In Pigsmentioning
confidence: 99%
“…However, despite the reported knowledge, we noticed clear the absence of information on the paths of infection and transmission of disease. This lack of knowledge may contribute to the persistence of porcine cysticercosis at households (Jayashi et al 2012). Ferreira et al (2012) observed that the lack of knowledge significantly favours the occurrence of porcine cysticercosis.…”
Section: Discussionmentioning
confidence: 99%
“…El país tiene diferentes regiones naturales, cada una con un perfil epidemiológico diferente. Por ejemplo, en la zona central del país hasta el 13,7% de la población puede tener serología positiva para cisticercosis 13 . Esta es una enfermedad de carácter regional y que afecta usualmente a poblaciones de bajos recursos.…”
Section: Discussionunclassified